Teacher profesionalism in fostering students’ creativity - Nurul Hidayah; Ardi Dwi Susandi; Naufalia Nuraya (CV. FOUNDAE, 2022)
Student creativity is essential to improve. One thing that affects this is the teacher's professionalism because it is the main factor in the success of student learning so that it produces and develops creativity. This study aims to describe the factors that increase student creativity and teacher efforts to increase student creativity. This study used a descriptive qualitative method. The data collection techniques were interviews with the subject teachers and principals, observation, and documentation. Furthermore, the technical data analysis used were data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that in the learning process, the teacher always plays a significant role so that students can develop their creativity. Four roles must be performed by the teacher: the teacher's role as a class manager; the teacher's role as an evaluator; the teacher's role as a facilitator; and the teacher's role as a demonstrator. In the learning process, the teacher always encourages his students. The teacher has also used learning media.